Changing patterns of Jhum cultivation in Tripura, India and their impact on malaria - Syed Shah Areeb Hussain; Kuldeep Singh; Gaurav Kumar; Suresh Chandra; Meenakshi Jeena; Shweta Pasi; Jaspreet Kaur (Journal of Global Health Reports)
# Background